2011
DOI: 10.1179/1743280411y.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

Role of materials surface topography on mammalian cell response

Abstract: Many approaches are used to modify the surface topography of implant materials. Some produce unordered surfaces using, for example, classical implant surface treatments, whereas others produce ordered surfaces by micro-and nanopatterning techniques. Surface topographies can be characterised by several methods that can acquire two-dimensional profiles or threedimensional measurements and calculate different roughness parameters. The importance of using systematically several roughness parameters for correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
115
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 316 publications
7
115
0
Order By: Relevance
“…These results may be due to the different cell sizes and origin. 42 According to what we have measured, the mean diameter of ESF-1 cells is 22 lm and almost in a round shape after just trypsinization, which is larger than HaCaT and HUVEC cells. So the d15-lm micropillar substrate may be not suitable for ESF-1 cells to attach.…”
Section: Effect Of the Micropillars On Cell Attachment And Prolifementioning
confidence: 63%
See 2 more Smart Citations
“…These results may be due to the different cell sizes and origin. 42 According to what we have measured, the mean diameter of ESF-1 cells is 22 lm and almost in a round shape after just trypsinization, which is larger than HaCaT and HUVEC cells. So the d15-lm micropillar substrate may be not suitable for ESF-1 cells to attach.…”
Section: Effect Of the Micropillars On Cell Attachment And Prolifementioning
confidence: 63%
“…These results may also indicate that cells could send local protrusions to probe the physical properties of the environment and later anchor themselves on the substrates that are suitable for their growth and proliferation. 42,43 In general, we found that the d18-lm micropillar substrate could prompt more cell adhesion and proliferation than the other substrates. In addition, cells on the d18-lm micropillar substrate showed higher cell viability and better morphology than those on the other substrates.…”
Section: Effect Of the Micropillars On Cell Attachment And Prolifementioning
confidence: 71%
See 1 more Smart Citation
“…5). The Ra values that characterise the substrates are within a range that has been shown to affect cell behaviour [58].…”
Section: Discussionmentioning
confidence: 98%
“…A review by Anselme and Bigerelle [58] states that, in the majority of studies, adhesion of bone cells increases when roughness increases, although other studies suggest otherwise. Chemistry appears to have no significant effect on cell adhesion.…”
Section: Discussionmentioning
confidence: 99%